Bad Girls - Tucker, Marcia; The New Museum of Contemporary Art, New York (Cambridge : the MIT press, 1994)
Agee, Ann ; Aguilar, Laura ; Akin, Gwen ; Antoni, Janine ; Bailey, Xenobia ; Ball, Lilian ; Barry, Lynda ; Berdann, Elizabeth ; Billops, Camille ; Bleiden, Molly ; Boadwee, Keith ; Bowers, Andrea ; Bowman, Lisa etc.
Bad Girls: An exhibition organized by Marcia Tucker at The New Museum of Contemporary Art, New York, Part I: January 14 - February 27, 1994 ; Part II: March 5 - April 10, 1994. Bad Girls West: An independent sister exhibition organized by guest curator Marcia Tucker for the UCLA Wight Art Gallery, Los Angeles, January 25 - March 20, 1994
boek